Pituitary Tumor Associated with Situs Inversus of the Optic Nerve Head - Williams, T. David (Canadian Journal of Optometry, 2018)
This report present further developments in a patient with an unusual vas-cular pattern on both optic nerve heads: the trunks of the central retinal vessels appear on the temporal side of the nerve head (situs inversus of the blood vessels of the nerve head). This vascular pattern was also present (to only slightly varying degrees) in all six of his children (two girls and four boys). Twenty-one years after the first presentation of this patient, he de-veloped a non-secretory pituitary tumor. This case suggests that congeni-tal nerve head anomalies may be markers for potential intracranial tumors later in life.